LAND SURFACE TEMPERATURE ANALYSIS AS AN INDICATOR OF URBAN HEAT ISLAND IN PADANG CITY - Hengki Sumantri; Noril Milantara; Teguh Haria Aditia Putra; Asvic Helida (Sylva Jurnal Ilmu-ilmu Kehutanan, 2025)
Padang City is the largest city on the west coast of Sumatra Island and the capital of West Sumatra Province, Indonesia (BPS Padang City, 2024). Surrounded by hills at an altitude of 1,853 meters above sea level, Padang covers an area of 1,414.96 km². The city had a population of 928,541 in mid-2023, comprising 11 sub-districts, 104 villages, and 19 small islands. Padang is the core city of the Palapa metropolitan area. This study aims to determine the comparison of surface temperatures in Padang City from 2014 and 2024. This research method consists of image data obtained from the USGS Explorer site consisting of Landsat 8 satellite images dated August 15, 2014 and January 23, 2024 and Band 10 and Band 11, and the administrative map of Padang City obtained from the boundaries of the Regency/City of the Population and Civil Registration Office (Dukcapil) of Padang City. The results of this study are that the land surface temperature in the Padang City area has increased over a period of ten years along with the increase in built-up land and land use due to human activities. The increase in built-up land surface temperature and land use is spatially distributed in eleven sub-districts with an average temperature of >25.9 OC. In line with the increase in land surface temperatures caused by changes in temperature class ranges, nine areas in Padang City have a high potential to become sources of urban heat islands: Koto Tangah, Nanggalo, Kuranji, North Padang, West Padang, East Padang, South Padang, Lubuk Begalung, and Bungus Teluk Kabung Districts. Spatially, these nine areas are adjacent to each other or connected to one another.